Proposta de padronização dos processos regulatórios de cursos de graduação no âmbito da Universidade Federal de Santa Maria - Almeida, Douglas Flores de (2018)
The external evaluation of undergraduate courses is an important component of the National System for the Evaluation of Higher Education in Brazil (SINAES), constituting itself as an instrument to guarantee the provision of quality higher education, and as a basis for the development of regulatory procedures for authorization, recognition and renewal of course recognition. Thus, this paper presents a proposal for the organization of external evaluation and regulation processes for undergraduate courses at the Federal University of Santa Maria (UFSM). In order to do so, we sought to identify the main difficulties encountered by course coordinators involved in these processes through semi-structured interviews. The interview script covered 21 questions regarding the coordinators' professional experience, their views on SINAES and the operationalization of external evaluation and regulation processes. Subsequently, the interviews were analyzed based on the technique of content analysis. The content analysis is a set of techniques of analysis of the communications that aims to obtain by systematic procedures and objectives of description of the content of the messages that allow the inference of knowledge regarding the conditions of production / reception of those messages. The obtained results pointed to the identification of difficulties with the process of operationalization of the external evaluations, as well as the lack of knowledge on the part of the coordinators interviewed in relation to the SINAES. In addition, suggestions were made for the improvement of the organization of these processes and were pointed out in the interviews. In addition to the interviews, the mapping of the regulatory processes of the courses under the UFSM was done through the use of the Bizagi Process Modeler (BPMN) software, which allowed the creation of the proposed flows for the better organization of the processes. Finally, a survey was carried out on how to organize these processes in other Federal Institutions of Higher Education. Thus, the result of the work culminated in the consolidation and presentation of a manual for the organization of regulatory processes of undergraduate courses within the scope of UFSM.